2019
DOI: 10.3892/or.2019.7140
|View full text |Cite
|
Sign up to set email alerts
|

Fingolimod sensitizes EGFR wild‑type non‑small cell lung cancer cells to lapatinib or sorafenib and induces cell cycle arrest

Abstract: Epidermal growth factor receptor (EGFR) is a receptor tyrosine kinase and mutations in this gene are major drivers of lung cancer development. EGFR tyrosine kinase inhibitors (TKIs) are standard first-line therapies for patients with advanced non-small cell lung cancer (NSCLC) with activating EGFR mutations, but are not effective in patients with wild-type EGFR. In the present study, the cytotoxic effects of various TKIs against EGFR were investigated in wild-type NSCLC cells as single treatments or in combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Fingolimod also shifts macrophages to an anti-inflammatory M2 phenotype and modulates their proliferation, morphology, and cytokine release ( 233 ). Preclinical studies of fingolimod have indicated that this drug is safe, potentiates the effect of chemotherapy ( 192 , 195 , 196 , 200 , 201 , 234 ), and suppresses tumor growth by inducing apoptosis (increased cleavage of PARP and caspases, decreased Bcl-2 and Mcl-1 levels, and increased Bax levels) ( 176 , 177 , 179 , 181 , 182 , 187 , 189 , 194 199 , 203 , 204 , 206 ), autophagy (increased LC3-II, beclin-1, and Atg7 levels, and decreased p62 expression) ( 197 , 203 , 208 , 209 ), necrosis ( 183 , 210 ), cell cycle arrest (increased levels of cell cycle inhibitory proteins [p27 and p21]); and decreased expression of cyclin D1 and C-X-C motif chemokine receptor 4 [CXCR4]) ( 186 , 187 , 197 , 204 , 209 ). Fingolimod also increases ceramide levels ( 181 , 204 ), the proteasomal degradation of SPHK1 ( 182 ), inactivation of RhoA-GTPase ( 178 ), histone deacetylase (HDAC) activity ( 185 ), multidrug resistance protein 1 (ABCB1) levels ( 195 ), protein phosphatase 2A (PP2A) reactivation ( 196 , 205 , 206 ), and modulation of signaling pathways (VEGF ( 176 , 186 , 199 ), MMP2, MMP9, CD31, E-cadherin, β-catenin ( 176 ), estrogens ( 187 ), JNK ( 191 ), NF-κB ( 206 ), STAT3 ( 201 , 206 ), AMP-activated protein kinase (AMPK) ( 208 ), mTOR ( 208 ), Erk1/2 ( 182 , 186 , 189 , 191 , ...…”
Section: Fingolimodmentioning
confidence: 99%
“…Fingolimod also shifts macrophages to an anti-inflammatory M2 phenotype and modulates their proliferation, morphology, and cytokine release ( 233 ). Preclinical studies of fingolimod have indicated that this drug is safe, potentiates the effect of chemotherapy ( 192 , 195 , 196 , 200 , 201 , 234 ), and suppresses tumor growth by inducing apoptosis (increased cleavage of PARP and caspases, decreased Bcl-2 and Mcl-1 levels, and increased Bax levels) ( 176 , 177 , 179 , 181 , 182 , 187 , 189 , 194 199 , 203 , 204 , 206 ), autophagy (increased LC3-II, beclin-1, and Atg7 levels, and decreased p62 expression) ( 197 , 203 , 208 , 209 ), necrosis ( 183 , 210 ), cell cycle arrest (increased levels of cell cycle inhibitory proteins [p27 and p21]); and decreased expression of cyclin D1 and C-X-C motif chemokine receptor 4 [CXCR4]) ( 186 , 187 , 197 , 204 , 209 ). Fingolimod also increases ceramide levels ( 181 , 204 ), the proteasomal degradation of SPHK1 ( 182 ), inactivation of RhoA-GTPase ( 178 ), histone deacetylase (HDAC) activity ( 185 ), multidrug resistance protein 1 (ABCB1) levels ( 195 ), protein phosphatase 2A (PP2A) reactivation ( 196 , 205 , 206 ), and modulation of signaling pathways (VEGF ( 176 , 186 , 199 ), MMP2, MMP9, CD31, E-cadherin, β-catenin ( 176 ), estrogens ( 187 ), JNK ( 191 ), NF-κB ( 206 ), STAT3 ( 201 , 206 ), AMP-activated protein kinase (AMPK) ( 208 ), mTOR ( 208 ), Erk1/2 ( 182 , 186 , 189 , 191 , ...…”
Section: Fingolimodmentioning
confidence: 99%
“…FTY720 is a synthetic compound produced by modification of a metabolite from I. sinclairii and has strong anti-cancer activity. For example, FTY720 induces cell death in multiple cancer cells [ 1 , 2 , 3 , 4 ] and sensitizes cancer cells to chemotherapy and radiotherapy [ 5 , 6 , 7 , 8 ]. Interestingly, FTY720 has also been seen to increase non-apoptotic cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Combination treatment with lapatinib and FTY720 enhances growth inhibition in PDAC cells. Previously, we reported that combination treatment with FTY720 and the EGFR/HER2 inhibitor lapatinib or multikinase inhibitor sorafenib can show prominent growth inhibitory activity in NSCLC cells (18). In the present study, we focused on lysosomotropic drugs (36).…”
Section: Resultsmentioning
confidence: 96%
“…Although some studies have documented the induction of autophagy by FTY720 (19)(20)(21)(22), others have reported autophagy suppression (23)(24)(25)(26)(27). In our previous study, we reported that FTY720 could inhibit lysosomal function and autophagic flux in NSCLC cells (18). Additionally, FTY720 has been reported to induce lysosomal membrane permeabilization (LMP) and non-apoptotic death in human glioma cells (28).…”
Section: Lysosome-targeted Drug Combination Induces Multiple Organell...mentioning
confidence: 95%
See 1 more Smart Citation